Analysis of the Renal Protection and Antioxidative Stress Effects of Panax notoginseng Saponins in Diabetic Nephropathy Mice - Wei Mi; Min Yu; Shuying Yin; Yuhan Ji; Tala Shi; Ning Li (Journal of Immunology Research)
Objective. Diabetic nephropathy (DN), a diabetes-induced chronic complication, is the major trigger of end-stage renal disease. As the main active ingredient of Panax notoginseng (PNG), Panax notoginseng saponins (PNS) are crucial in treating renal diseases. This study is aimed at investigating the role played by PNS in renal protection and antioxidative stress (OS) in DN mice. Methods. A DN mouse model was constructed, and then low, medium, and high doses of PNS were used to intervene the model group mice. Eight weeks after intervention, the 24 h urine protein (UPro) and urinary albumin (UAlb) were quantitatively examined, and the related blood biochemical indices were measured. HE and PAS staining were performed for pathological changes of renal tissue. ELISA and western blotting were carried out to quantify the levels of OS indexes and inflammatory factors (IFs) in mouse kidney tissues and the expression of nuclear factor erythroid 2-related factor 2 (Nrf2) and heme oxygenase-1 (HO-1), respectively. Results. The weight of DN mice decreased first compared with control animals and then gradually increased after different doses of PNS treatment. Besides, DN mice presented elevated urine volume, UPro, and UAlb, all of which were reversed by PNS intervention. SOD activity and GSH content in renal tissues of the model group mice decreased markedly versus the control group, and MDA, CRP, IL-6, and TGF-β1 contents elevated statistically, while different doses of PNS effectively reduced the OS injury and IFs in mice. Compared with the model group, PNS dose-dependently increased Nrf2 and HO-1 levels in DN mice. Conclusions. PNS is protective of HFF + STZ-induced DN mice against kidney tissue damage and can reduce the excretion of UPro and relieve the OS state of mice, possibly by activating Nrf2/HO-1 axis to play an antioxidant and anti-inflammatory role.